Peran Kaligrafi Dalam Pendidikan Islam Seni Dan Moralitas - M. Dzaki Sholihin; Johar Kurniawan Siagian (Al-Abshor : Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the meaning, function, and development of calligraphy in Islam, as well as its role as a spiritual, educational, and moral medium. This study also aims to analyze the contribution of calligraphy in shaping the Islamic character of students, identify the moral values contained therein, and evaluate the relevance and challenges of developing calligraphy in the modern era, particularly in the context of Islamic education. This research uses a qualitative method, a structured and systematic research method that aims to investigate, select, evaluate, and integrate relevant literature from various sources. This research also uses a library research approach that focuses on collecting and analyzing data from various literature sources, such as books, scientific journals, articles, official documents, and other relevant written sources. The analysis results indicate that calligraphy in Islam is a combination of visual beauty and deep spiritual meaning. This art serves as a means for da'wah, worship, and education. Since the early days of Islamic civilization, calligraphy has developed rapidly and reached extraordinary development during the Abbasid period, where figures such as Ibn Muqlah played an important role. In terms of education, calligraphy helps shape an individual's character through the practice of patience, discipline, and love for the Qur'an. Additionally, calligraphy teaches moral values such as monotheism, piety, and humility. In the modern era, calligraphy remains significant despite the emergence of technology and contemporary art, though it faces various challenges in its application. Therefore, support from educational institutions and society is essential to ensure that this art form remains alive as part of Islamic cultural and spiritual heritage. Abstrak Penelitian ini bertujuan untuk untuk mengkaji makna, fungsi, dan perkembangan seni kaligrafi dalam Islam, serta peranannya sebagai media spiritual, pendidikan, dan moral. Penelitian ini juga bertujuan untuk menganalisis kontribusi kaligrafi dalam membentuk karakter Islami siswa, mengidentifikasi nilai-nilai moral yang terkandung di dalamnya, serta mengevaluasi relevansi dan tantangan pengembangan kaligrafi di era modern, khususnya dalam konteks pendidikan Islam. Metode penelitian ini menggukan metode kualitatif, sebuah metode penelitian yang terstruktur dan sistematis yang bertujuan untuk menyelidiki, memilih, mengevaluasi, dan mengintegrasikan literatur yang relevan dari berbagai sumber, penelitian ini juga menggunakan pendekatan library research yang berfokus pada pengumpulan dan analisis data dari berbagai sumber literatur, seperti buku, jurnal ilmiah, artikel, dokumen resmi, dan sumber-sumber tertulis lainnya yang relevan. Hasil analisis menunjukkan bahwa Seni kaligrafi di dalam Islam adalah kombinasi antara keindahan visual dan makna spiritual yang dalam. Seni ini berfungsi sebagai sarana untuk dakwah, ibadah, dan pendidikan. Sejak zaman awal peradaban Islam, kaligrafi telah berkembang dengan pesat dan mencapai perkembangan luar biasa pada masa Abbasiyah, di mana tokoh seperti Ibnu Muqlah memainkan peran penting. Dalam hal pendidikan, kaligrafi membantu membentuk karakter individu melalui latihan kesabaran, kedisiplinan, dan rasa cinta terhadap Al-Qur’an. Selain itu, kaligrafi juga mengajarkan nilai-nilai moral seperti tauhid, ketakwaan, dan kerendahan hati. Di zaman modern saat ini, kaligrafi tetap memiliki pentingnya dengan adanya teknologi dan seni kontemporer, meskipun menghadapi berbagai tantangan dalam penerapannya. Oleh karena itu, dukungan dari lembaga pendidikan dan masyarakat sangat diperlukan agar seni ini tetap hidup sebagai bagian dari warisan budaya dan spiritual Islam.